Western european researchers on the conditions of effective transformation of a teacher's professional habitus during the seminars analyzing practices - Kharchenko Tetiana; Zvereva Maryna (Borys Grinchenko Kyiv Metropolitan University, 2018)
The article deals with the notion of «habitus». It means a combination of codes and abilities obtained in an early age, the way an individual applies them under different conditions. It dwells upon the studies of Western European researchers of education theory and practice on the conditions of effective transformation of a teacher's professional habitus. One of the conditions is the implementation of a global clinic approach understood as a permanent alteration of theory and practice in the teacher training process. They argue that theoretical knowledge accumulated beyond the context of actions is not possible to mobilize and is not mobilized to solve professional problems. There are five important issues of organizing the teacher clinic training suggested by the Western European researchers of theory and practice of education in the late 20th century. One of them is the organization of collective analysis seminars on practices within the professional educational training. According to the above mentioned researchers, participating in a group analyzing practices serves as an introduction to the personal reflective practice and stimulatesthe development and transformation of the personality of reflexive teacher-practitioner (in other words, the development and transformation of the teacher, possessing developed reflexive skills, directed onto self-analysis of his or her own professional actions, behavior style, internal state; this is the teacher who is able to make professional decisions and to act by himself or herself; this is the one who takes responsibility for his or her decisions and actions.) The article reveals the conditions when the collective analysis of practices can enhance changes in educational practices and behavior of a teacher. In their opinion, the teacher's personality changes can be possible provided the analysis of the practices is relevant, accepted by a teacher and integrated by him or her into the professional activity.